ANALISIS STRATEGI PEMASARAN PERUMAHAN DI MAKASSAR (Studi Kasus PT Indah Bumi Bosowa) - Mukhtar Galib (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2017)
This research aimed to : (1) to know the storey level of excellence of competition PT IBB so that can expand a period of to come (2) to know the accuracy of marketing strategy conducted by PT. IBB in maximizing ability and its weakness minimization to exploit the opportunity and lessen the threat faced. This research represent the case study. Technique the data analysis used is : descriptive statistical analysis of BF-ALBA, the SWOT analysis, I-E Matrix and matrix TOWS /SWOT with analysing various factor of external and internal company logically and systematic. The results of this research showed that : (1) through the descriptive statistical analysis of BF-ALBA obtained a mean score from fifth of industrial real estate emulation variable that is, new comer, emulation in industry, distribution of housing requirement, buyer and substitution goods of equal to 9,80 or 32,67% from maximal score. This score be at the low category meaning PT. IBB have the low excellence competitive. (2) analysis of marketing strategy with the SWOT method analysis, so that PT. IBB have the big market opportunity. Nevertheless PT.IBB have the internal weakness. In a condition like this company better use the strategy of development of market turn-around that is internal problem minimization of company so that can grab the market. From I-E Matrix look that PT.IBB be at the cell of growth and build. Matter this means strategy which better be conducted by a company is intensive strategy like market development, penetrating of market and product development housing